2003
DOI: 10.1055/s-2003-41057
|View full text |Cite
|
Sign up to set email alerts
|

Detritylation Procedure under Non-Acidic Conditions: Naphthalene Catalysed­ Reductive Cleavage of Trityl Ethers

Abstract: The reaction of primary, secondary, allylic and benzylic trityl ethers 1 with lithium powder and a catalytic amount of naphthalene led to reductive cleavage of the trityl-oxygen bond, affording the corresponding alcohols 2 in good to excellent yields under very mild reaction conditions. The detritylation process could successfully be extended to several hydroxy, alkoxy and amino functionalised trityl ethers. This methodology represents a new and efficient detritylation procedure under non-acidic reaction condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In the last few years, our group has been interested in the deprotection of several functional groups using naphthalene-catalyzed lithiation, 15 including trityl ethers, 16 trityl amines, 17 silylated alcohols, amines and thiols, 18 Alloc-or Cbz-or Boc-protected alcohols, amines or thiols, 19 esters, amides and thioesters, 20 and N-pivaloyltetrazoles. 15l Other metals, such as indium 21 In the present paper we describe the deprotection of trityl protected alcohols and diols with lithium chloride.…”
Section: Dedicated To Professor Joaquín Plumet On Occasion Of His Retmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, our group has been interested in the deprotection of several functional groups using naphthalene-catalyzed lithiation, 15 including trityl ethers, 16 trityl amines, 17 silylated alcohols, amines and thiols, 18 Alloc-or Cbz-or Boc-protected alcohols, amines or thiols, 19 esters, amides and thioesters, 20 and N-pivaloyltetrazoles. 15l Other metals, such as indium 21 In the present paper we describe the deprotection of trityl protected alcohols and diols with lithium chloride.…”
Section: Dedicated To Professor Joaquín Plumet On Occasion Of His Retmentioning
confidence: 99%
“…They were fully characterized by comparison of their spectroscopic data with authentic samples. 16 The reaction was first examined using trityl ether 1a with LiCl (1:1 molar ratio) in DMSO at reflux for 24 h, 24 however the reaction failed and the starting material was recovered. However, the same reaction conducted in MeOH at reflux for 12 h afforded the expected alcohol 2a in 88% yield ( Table 1, Entry 1).…”
Section: Dedicated To Professor Joaquín Plumet On Occasion Of His Retmentioning
confidence: 99%
“…The trityl ( triphenylmethyl ) group has also been extensively used as a protecting group of alcohols and it can easily be removed by acidic hydrolysis. However, it has been reported that the reaction of alkyl (primary or secondary) allylic and benzylic trityl ethers (91) with Li powder and a catalytic amount of naphthalene produces the reductive cleavage of the trityl -oxygen bond, affording the corresponding alcohols (92) in good to excellent yields under mild reaction conditions (Scheme 17.32 ) [103] .…”
Section: Reduction Of C -O To C-h Bondsmentioning
confidence: 99%
“…11,12,13 Among other uses, 14 this methodology has been shown to be applicable to the cleavage of trityl ethers 15 and amines, 16 to the desilylation 17 and the deallyloxy-or debenzyloxycarbonylation 18 of protected alcohols, amines and thiols, and to perform the deacylation of esters, thioesters and amides. 19 In this paper we report on the reductive removal of the Boc group from protected alcohols, amines and thiols via a DTBB-catalysed lithiation process under very mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%